Complete genome sequence of Pandoraea thiooxydans DSM 25325T, a thiosulfate-oxidizing bacterium - Yong, D.; Ee, R.; Lim, Y.L.; Yu, C.Y.; Ang, G.Y.; How, K.Y.; Tee, Kok Keng; Yin, Wai Fong; Chan, Kok Gan (Elsevier, 2016)
Pandoraea thiooxydans DSM 25325T is a thiosulfate-oxidizing bacterium isolated from rhizosphere soils of a sesame plant. Here, we present the first complete genome of P. thiooxydans DSM 25325T. Several genes involved in thiosulfate oxidation and biodegradation of aromatic compounds were identified.